Development of a Reference Standard of Escherichia coli DNA for Residual DNA Determination in China - Wang, Lan (Public Library of Science, 2013)
This collaborative study developed the first national Escherichia coli (E. coli) DNA reference standard for standardizing quantitative residual DNA assay methods, fluorescence dye (PicoGreen) and quantitative PCR (q-PCR), which were widely employed to measure residual DNA contents of prokaryotic-derived recombinant products. High purity of E. coli strain BL21 was extracted by the cetyl triethyl ammonium bromide (CTAB)/phenol chloroform method, analyzed by UV-visible spectrophotometry and electrophoresis, diluted with tris-EDTA (TE) buffer and manually dispensed. Then, with a cooperative calibration among six laboratories, including five manufacturers and one national control laboratory, the concentration of E. coli DNA standard solution was determined as 96.2 μg/mL (95% C.I: 95.5–96.9 μg/mL, CV 3.4%). The candidate showed excellent stability both from accelerated degradation study and real time stability study. The applicability study showed that the E. coli DNA reference could reach the sensitivity of 0.781 ng/mL and 1 fg/μL, respectively, in fluorescent dye and q-PCR assay, and also had good linearity and precision. The consistency of the reference could meet the requirements of the national reference standard. As a conclusion, the candidate material was suitable to serve as a China national standard for E. coli residual DNA determination. The successful establishment of the E. coli DNA standard will facilitate the standardization of quantitative methods for testing residual host cell DNA.